2015
DOI: 10.1039/c5ee00938c
|View full text |Cite
|
Sign up to set email alerts
|

Varying the ionic functionalities of conjugated polyelectrolytes leads to both p- and n-type carbon nanotube composites for flexible thermoelectrics

Abstract: Selective doping of single-walled carbon nanotubes can be achieved by varying pendant ionic functionalities of conjugated polyelectrolytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
115
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(125 citation statements)
references
References 64 publications
10
115
0
Order By: Relevance
“…It is worth noting that the measured value of the Seebeck coefficient of the pencil-drawn film on paper S G is comparable to that of other expensive electron-conducting nanocomposite materials used in flexible thermoelectric devices (−21 μV K −1 ). 10 Thus, it is conceivable that the combination of pencil traces and PEDOT:PSS films on electrically and thermally insulating paper substrate can be used for a novel inexpensive and flexible thermoelectric device architecture.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that the measured value of the Seebeck coefficient of the pencil-drawn film on paper S G is comparable to that of other expensive electron-conducting nanocomposite materials used in flexible thermoelectric devices (−21 μV K −1 ). 10 Thus, it is conceivable that the combination of pencil traces and PEDOT:PSS films on electrically and thermally insulating paper substrate can be used for a novel inexpensive and flexible thermoelectric device architecture.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The Seebeck coefficient of graphite pencil-drawn films was negative and with a reasonably high value of S G = −17.5 μV K −1 comparable to other expensive electron-conducting nanocomposite materials used in flexible thermoelectric devices (−21 μV K −1 ). 10 This allowed to draw graphite pencil trace/ PEDOT:PSS thermoelectric elements on regular office paper. The fabrication of multijunction thermoelectric power generators can be realized by drawing arrays of interconnected graphite pencil trace/PEDOT:PSS thermoelectric elements.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…The donor impurities correspond to the nitrogen atoms substitutionally incorporated during production of the CNTs, whereas the P3HT wrapped around the nanotubes is assumed to effectively act as an acceptor, injecting holes into the CNT valence band, as was very recently shown for CNT composites with polyelectrolytes. [ 45 ] The actual position of the Fermi level in the CNTs at a given temperature simply results from the difference in effective donor-and acceptor-level densities by invoking charge neutrality. [ 46 ] This determines the type of the majority carriers in the system, and in turn, the sign of the Seebeck coeffi cient as is explained in more detail in the discussion of Figure S3 (Supporting Information).…”
Section: Doi: 101002/adma201505521mentioning
confidence: 99%
“…18 Therefore, we first verified the type of p-or n-doping dependence on CPE structure. Seebeck coefficient measurements showed that holes (positive S) and electrons (negative S) are the major charge carriers in CPE-Na/SWNT and CPE-PyrBIm 4 /SWNT, respectively.…”
Section: Resultsmentioning
confidence: 99%